Nationwide study on peripheral-venous-catheter-associated-bloodstream infections in internal medicine departments. Issue 3 (November 2017) - Guembe, M.; Pérez-Granda, M.J.; Capdevila, J.A.; Barberán, J.; Pinilla, B.; Martín-Rabadán, P.; Bouza, E.; ,
Summary: Background: The use of peripheral venous catheters (PVCs) has increased outside intensive care units, as has the rate of PVC-associated-bloodstream infection (PVC-BSI). PVCs are widely used in internal medicine departments (IMDs), but data on the incidence of PVC-BSI and its characteristics in IMDs are scarce. Aim: To assess the incidence of PVC-BSI episodes detected in IMDs in Spain. Methods: A one-year multi-centre prospective observational cohort study in 14 Spanish IMDs was undertaken. Adult patients admitted with at least one PVC and bacteraemia were included in the study. Demographic and clinical data were provided by local coordinators. Findings: Seventy episodes of PVC-BSI were recorded, representing an overall rate of 1.64 PVC-BSI episodes/1000 IMD admissions. The mean age of patients was 67.44 (standard deviation 16.72) years. It was estimated that 25.7% of PVCs were no longer necessary. Staphylococcus aureus was the most frequently isolated micro-organism (41.7%). Phlebitis was clinically evident in 44 (62.9%) episodes, and proved to be an independent predictor of catheter insertion in emergency departments (odds ratio 5.44). The crude and attributable mortality rates were 12.9% and 5.7%, respectively. Conclusions: PVCs carry a significant risk for bacteraemia in Spanish IMDs. Phlebitis is not always clinically evident in patients with bacteraemia in this population. The study findings support the need for educational and interventional preventive measures in both IMDs and emergency departments to reduce the rate of PVC-BSI and associated comorbidities, and costs.